Does leadership style matter in change management success? Employee performance as a proxy of effective change / Kee Swee Lin ... [et al.] - Kee, Swee Lin; Ramayah, T.; Dahlan, Noornina; Lo, May Chiun (Faculty of Business and Management ; UiTM Press, 2007)
Past researchers have indicated that an effective change requires influencing employees positively and accomplishing group objectives. Managing change effectively in an organization is dependent on various factors and one of them is leadership style. The main purpose of this paper is to investigate the change effectiveness' dependence on leadership style. Data collected using a structured questionnaire showed that leadership style does influence effectiveness of change although out of the 3 styles used only one; participative leadership style was a significant predictor of success. The paper outlines a clear link between various leadership styles and the success of change management. Furthermore this paper identifies a major new source of strategic leadership value added in the companies' attention to creating processes and encouraging efforts for change management. Implications of the findings, potential limitations of the study, and directions for future research are suggested.